Wilms tumour in a two day old neonate: A rare and challenging case - Ravel, Naveen; Rajan, Teena; K, Mohankumar; Vadivelu, Gomathy; PN, Sathiyamoorthi; Ramanan, Arun; P, Vijayaraghavan; Joel, Sam M; Chodavarapu, Dheeraj; Konduri, Meena; Pothala, Vijayalakshmi (Indian Journal of Case Reports, 2024)
Wilms tumor or nephroblastoma is the second most common renal tumor occurring in the neonatal age group next to congenital mesoblastic nephroma. The most common age group of presentation of Wilms tumor is between 3 and 4 years of age. Here, we report a case of right-sided Wilms tumor in a 2-day-old neonate. A term-born female baby presented on day 2 of birth with abdominal distension and physical examination revealed a large palpable mass in the right lumbar region crossing the midline. Imaging features were suggestive of a retroperitoneal mass of probable right renal origin. The patient was taken up for right radical nephroureterectomy and Per-operatively, there was anticipated tumor spillage. Post-operative histopathological examination was suggestive of a triphasic Wilms tumor with no anaplasia and favorable histology. The patient was diagnosed with Wilms tumor of the right kidney, COG stage III, SIOP (“International Society of Pediatric Oncology”) intermediate risk loss of heterozygosity testing for 1p and 16q was negative. She was started on chemotherapy with a DDA4 regimen. She completed whole abdominal radiotherapy and tolerated treatment well. The child is disease free and is under regular follow-up. This case of neonatal Wilms tumor was indeed a challenge to the pediatric surgeons and the oncologists but the final results were worth the challenge that was faced.